Evaluation of the Long-Term Impact on Quality After the End of Pharmacist-Driven Warfarin Therapy Management in Patients With Poor Quality of Anticoagulation Therapy - Marcatto, Leiliane Rodrigues; Sacilotto, Luciana; Tavares, Letícia Camargo; Souza, Debora Stephanie Pereira; Olivetti, Natália; Strunz, Celia Maria Cassaro; Darrieux, Francisco Carlos Costa; Scanavacca, Maurício Ibrahim; Krieger, Jose Eduardo; Pereira, Alexandre Costa; Santos, Paulo Caleb Junior Lima (Frontiers in Pharmacology, 2020)
Background: Warfarin is the most commonly drug for oral anticoagulant therapy, especially in low-income and emerging countries, because of the high cost of the direct oral anticoagulant (DOACs) or when warfarin is the only proven therapy (mechanical prosthetic valve and kidney dysfunction). The beneficial outcomes of warfarin therapy are directly dependent on the quality of anticoagulation management and dose regimen. Studies showed that pharmacists could improve the effectiveness of therapy with warfarin. However, there are no studies showing this intervention in a specific patient group with poor quality of anticoagulation in a long period after the end of the follow-up by a pharmacist. Thus, the aim of this study was to evaluate whether the quality of warfarin therapy driven by a pharmacist remains in a long term after the end of follow up with pharmacist, in patients with AF and poor quality of anticoagulation. Methods: This is a prospective study which evaluated about 2,620 patients and selected 262 patients with AF and poor quality of anticoagulation therapy with warfarin (TTR<50% - based on the last three values of international normalized ratio). Pharmacist-driven therapy management was performed for up 12 weeks. Data from patients were evaluated 1 year after the end of the follow-up with pharmacist. Results: Comparison between mean TTR 12 weeks of pharmaceutical care (54.1%) and mean TTR one year after the end of the pharmaceutical care (56.5%; p=0.081), did not achieved statistical difference, demonstrating that the increment of quality due to intervention of 12 weeks was maintained for 1 year after intervention. Conclusion: The long-term impact of the pharmaceutical care was beneficial for patients with AF and poor quality of warfarin anticoagulation. This design might be an important strategy to treat a subgroup of patients without proven effectiveness of warfarin or when DOACs are not economic viable or available in public health.